Ethics of disclosure of onset‐predictive biomarker test results for genetic frontotemporal dementia in the research context - Charlotte H. Graafland; Laura Donker Kaat; Edo Richard; John C. vanSwieten; Harro Seelaar; Eline M. Bunnik (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract Onset‐predictive biomarker tests (OPBTs) for genetic frontotemporal dementia (FTD) may predict symptom onset in coming years. OPBT results could be used as inclusion criterion for clinical trials for FTD, but this requires disclosure of OPBT results to potential participants for informed consent. This creates a dilemma, as disclosure may be psychologically burdensome. Yet, individuals at risk of FTD may value OPBTs to relieve uncertainty and support planning for the future. This article provides an overview of considerations regarding disclosure using four themes (actionability, respect for autonomy and informed consent, psychological impact, social and societal impact), based on literature on return of individual research results and biomarker disclosure in Alzheimer's disease. Based on this, we argue that clinical validity and context of use are important considerations, and suggest that (1) counseling facilitates informed decision making, (2) clinical and psychological follow‐up provides necessary support, and (3) impacts may be monitored in a pilot study. Highlights Ethical considerations regarding disclosure of onset‐predictive biomarker test (OPBT) results include actionability, respect for autonomy and informed consent, psychological impact, and social and societal impact. The weight of each consideration depends heavily on the clinical validity of the OPBT results and the context of use. OPBT result disclosure to individuals at risk of genetic frontotemporal dementia (FTD) for clinical trial recruitment seems ethically acceptable. We suggest embedding OPBT results disclosure in counseling, follow‐up, and a pilot study on impacts of OPBT results disclosure.